1985
DOI: 10.1590/s0074-02761985000400009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ivermectin against the bloodsucking insect, Rhodnius prolixus (Hemiptera, Triatominae)

Abstract: Ivermectin (0.2 mg/kg body weight) caused a high mortality in nymphs and adults of Rhodnius prolixus following a single meal in mice sub-cutaneously injected with the drug. This effect was more evident in nymphs of 1st-and 2nd-instar than in older nymphs and adults. Third-instar nymphs presented a high mortality when fed on mice treated with ivermectin 24 and 48 hours previously, while mortality was significantly reduced in nymphs fed on mice treated 72 hours before. Surviving 3rd-instar nymphs did not molt. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
11
0
3
Order By: Relevance
“…Clements (1996) have pointed out that some increase in cellular size occurs with the accumulation of lipids and glycogen, while the storage of proteins is associated with a considerable increase in the volume of the fat body cells. Decrease in egg production was also observed in Rhodnius prolixus females exposed to ivermectin (De Azambuja et al, 1985). Involvement of vitellogenesis with the ivermectin can also affect polyamines synthesis in C. quinquefasciatus, because this synthesis is one of the first events of the yolk formation in Aedes aegypti (Kogan and Hagedorn, 2000).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Clements (1996) have pointed out that some increase in cellular size occurs with the accumulation of lipids and glycogen, while the storage of proteins is associated with a considerable increase in the volume of the fat body cells. Decrease in egg production was also observed in Rhodnius prolixus females exposed to ivermectin (De Azambuja et al, 1985). Involvement of vitellogenesis with the ivermectin can also affect polyamines synthesis in C. quinquefasciatus, because this synthesis is one of the first events of the yolk formation in Aedes aegypti (Kogan and Hagedorn, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…Sub-lethal effects of insecticide acts within three categories: feed inhibition, development abnormalities and reproductive disturbances (Strong and Brown, 1987). Sub-lethal effects of avermectins were observed on the reproduction of Rhodnius prolixus (De Azambuja et al, 1985) and on the development inhibition of Chrysomya bezziana and Calliphora vomitoria (Spradbery et al, 1985;Strong, 1986). In Diptera and Coleoptera, there are reports about water accumulation in the individuals as consequence of the avermectin action suggesting that the drug has interference in the Malpighian tubules and hormones that acts on water balance (Strong, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the reported effects of avermectins on arthropods are on the peripheral nervous system, several authors have suggested that the secondary effects on insect growth, development, and reproduction are due to effects on the neurosecretory cells (Glancey et al 1982, De Azambuja et al 1985, Antunes et al 2005. In the American lobster, we hypothesized that emamectin benzoate interferes with the neuroendocrine control of the molting glands (Y organs; Waddy et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment induced high mortality of Triatoma and Rhodnius, this was largely restricted to bugs feeding within 24 h of the ivermectin treatment. It would appear that metabolism of ivermectin during the first 48 h after treatment (Azambuja et al 1985, Paradis 1998, results in concentrations too low to offer a sustained effect against Triatominae.…”
Section: Discussionmentioning
confidence: 99%
“…For this, all the dogs were treated with subcutaneous injections of ivermectin (Detomax ) at 20 mg a.i./kg. Ivermectin is the 22,23-dihydro derivative of avermectin B 1 , a macrocyclic lactone produced by the actinomycete Streptomyces avermitilis, which is active against a wide variety of nematode and arthropod parasites (Campbell et al 1983, Azambuja et al 1985, Campbell 1985, Rey 1991, Cimermann & Cimermann 1999, Barbosa & Campos 2001, PAHO 2001. The present data are a product of a casual situation, in which some dogs experimentally infected with T. cruzi became infested by R. sanguineus, so providing the opportunity to observe the possibility of a natural infection of ticks by that flagellate, as well as the eventual action of ivermectin against triatomines and trypanosomes.…”
Section: Methodsmentioning
confidence: 99%